Pelatihan Inspection Preventive Maintenance (IPM) MRI - Nani Lasiyah; M. Rio Oktaviano; Yeni Pertiwi; Nurhadziqoh; Romi Mulyadi; Rino Ferdian (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
In Indonesia, the quality assurance of medical devices is carried out by the Hospital Facility Maintenance Installation, abbreviated as IPSRS. Generally, IPSRS staff consists of Human Resources (HR) who have qualifications in Electromedical, Public Health, and Management qualifications. Human resources in charge of carrying out maintenance and repairs, hereinafter referred to as Preventive Maintenance Inspections (IPM) of medical devices, are human resources with electromedical qualifications. Magnetic Resonance Imaging (MRI) is an advanced medical device that combines computer technology, high magnetic fields (0.067.0 Tesla) and radio waves to produce cross-sectional images of the muscles of the human body. To prepare patient services in hospitals using an MRI tool, reliable human resources are needed in carrying out their HDI. For this reason, training on the HDI of this MRI equipment is needed. This HDI training was attended by 534 participants from all over Indonesia which was carried out through the Zoom Meeting Application. This training succeeded in increasing the ability of participants by 27.98% while the average satisfaction of training participants was assessed from 5 aspects, namely at 86.65%, so that the training carried out is in the very satisfactory category.